Comparison of Intramuscular Versus Rectal Diclofenac Sodium in Post Caesarean Pain Relief - Beenish Altaf; Sanum Kashif; Shagufta Saeed Sial; Humera Noreen; Erum Pervaiz; Shazia Mahmood Awan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the mean post-operative pain after intramuscular versus rectal Diclofenac Sodium in post-caesarean patients.